PENGARUH KOMITMEN MANAJEMEN, TEKANAN EKSTERNAL, KETIDAKPASTIAN LINGKUNGAN DAN GAYA KEPEMIMPINAN TERHADAP PENERAPAN TRANSPARANSI PELAPORAN KEUANGAN DENGAN AKUNTABILITAS SEBAGAI VARIABEL PEMODERASI (Studi Empiris Pada Organisasi Perangkat Daerah Kabupaten Kampar) - Fatima Elana; Andreas Andreas; Rusli Rusli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to examine the effect of management commitment, external pressure,environmental uncertainty and leadership style on the implementation of financialreporting transparency with accountability as a moderating variable. This research is aquantitative research. The population in this study were 25 Regional ApparatusOrganizations (OPD) in Kampar Regency. The sample in this study used the conveniencesampling method. The type of data used in this study is primary data. Data collectiontechniques using a questionnaire consisting of 3 respondents so that a total of 75questionnaires were distributed. The analytical method used is Multiple RegressionAnalysis using the SPSS version 25.00 program. The statistical results in this study showthat the variables of management commitment, external pressure, environmentaluncertainty, leadership style on the implementation of financial reporting transparencyhave an effect and the accountability variable moderates the independent variables on theimplementation of reporting transparency. finance . Keywords: Management Commitment, External Pressure, Environmental Uncertainty,Leadership Style, Financial Reporting Transparency and Accountability.